AN EMPIRICAL RESEARCH ON LEGAL AWARENESS AMONG THE UNIVERSITY STUDENTS IN AZERBAIJAN - Khalilova Tayba Rauf (International Journal of Innovative Technologies in Social Science, 2025)
Legal concepts and legal awareness are one of the main components of social awareness. This research devoted to study the students’ legal awareness mainly focuses on their attitudes to laws and components of legal awareness. Although legal awareness is a big complex, each of the component can be evaluated individually. The present study examines the students’ approach and their awareness about legal issues, and their rights. The methodology of the study was developed based on constructivist approach, and the main tool of the research - survey questions assess the cognitive component of legal awareness. The study was realized at Faculty of Social science and psychology, Baku State University in 2025. The results, and relation between dependent and independent variables were analyzed using SPSS program. The verification of the research questions reveals statistically significant positive results. These findings enable us to assume that the more developed legal concepts are, the more correctly learners apply the knowledge of the relevant laws to recognize situations with unlawful behaviour. The obtained results can be taken into account in developing training programs to increase the legal awareness of students at the university community.